Bone neoformation in defects treated with platelet-rich fibrin membrane versus collagen membrane: a histomorphometric study in rabbit femurs. - Edwin Meza; Emil Correa; David Soto; Liz Ríos (Universidad de Concepción., 2015)
The aim of the present research was to compare bone neoformation in bone defects treated with platelet-rich fibrin (PRF) and collagen membrane (CM) at 3 and 5 weeks. For this purpose, two bone defects with a width of 4 mm and depth of 6 mm were created in the left distal femur diaphysis of New Zealand rabbits (n=12). The subjects were randomly allocated into two groups. One of the defects was covered with a platelet-rich fibrin membrane (Centrifuged resorbable autologous blood biopolymer without biochemical modification) or a collagen membrane (gold standard - Neo Mem). The second defect was left uncovered (NC). The rabbits were sacrificed after 3 and 5 weeks (3 rabbits per period). The femur was completely removed and processed histomophometrically. The bone neformation analysis was performed using a differential point-counting method. Data was statistically analyzed (ANOVA, Tukey). The histomorphometric results showed that bone neformation in the defects treated with PRF at 3 weeks was equivalent to the CM (p<0.05). After 5 weeks, bone neformation obtained with PRF was higher than the control group and lower compared with the CM (p<0.05). The conclusion of the present study is that bone neformation in defects treated with PRF showed lower histomorphometric results compared with the one obtained with the collagen membrane and higher when compared with the control defects.